Pengembangan Ekonomi Lokal Berdasarkan Modal Sosial Melalui Komunitas Petambak - Muis, Abd (SIGn Journal of Social Science, 2022)
This study aims to determine the contribution of social capital to farmer communities in the local economic development of aquaculture in Purworejo Village, Pasir Sakti Subdistrict, East Lampung Regency. This research was conducted using a qualitative approach. Observation and interviews were used to obtain the data needed in this study. The data that has been obtained is then analyzed using qualitative inductive analysis. The results show that the social capital of farmer communities in local economic development in Purworejo Village gave a substantial contribution. The contribution can be described in three aspects of social capital: horizontal network, reciprocity norms, and the principle of trust. Therefore, it is recommended that the fishery cultivation group looks at the opportunities and challenges of utilizing social capital in local economic development in Purworejo Village. Thus, local economic development will further improve the welfare of the people of Purworejo Village in the future.